Long-chain polyunsaturated fatty acid status in children, adolescents and adults with phenylketonuria - Gramer, Gwendolyn; Haege, Gisela; Langhans, Claus-Dieter; Schuhmann, Vera; Burgard, Peter; Hoffmann, Georg F. (Prostaglandins, leukotrienes and essential fatty acids, 2016)
Background - Patients with phenylketonuria have been reported to be deficient in long-chain polyunsaturated fatty acids (LCPUFAs). It has been postulated that good compliance with the dietary regimen negatively influences LCPUFA status. - Methods - In 36 patients with phenylketonuria and 18 age-matched healthy control subjects LCPUFA-levels in plasma phospholipids and cholesteryl esters, erythrocyte phosphatidylcholine and phosphatidylethanolamine were evaluated. - Results - Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels did not differ significantly between patients and control subjects in plasma and erythrocyte fractions. There was a significant negative correlation between SDS (standard deviation) scores of DHA-levels in erythrocyte parameters from the respective age-matched control group and patients’ concurrent and long-term phenylalanine levels for erythrocyte phosphatidylethanolamine and erythrocyte phosphatidylcholine. Patients with lower (higher) phenylalanine levels had positive (negative) DHA-SDS. - Conclusion - In contrast to previous reports we did not find lower LCPUFA-levels in patients with phenylketonuria compared to age-matched healthy control subjects. Good dietary control was associated with better LCPUFA status.